Analisis Kelayakan Usahatani Kakao di Desa Kopandakan Dua Kecamatan Lolayan Kabupaten Bolaang Mongondow - Dosa, Muhamad Fahriyaldi; Porajow, Oktavianus; Pangemanan, Lyndon Reindhart Jacob (Sam Ratulangi University, 2023)
This study aims to analyze the financial feasibility of cocoa farming in Kopandakan II Village, Lolayan District, Bolaang Mongondow Regency. This research was conducted from October to November 2022. Data collection in the field was carried out by purposive sampling by direct interviews and data from the Central Bureau of Statistics for Bolaang Mongondow Regency, institutions related to cocoa commodity and scientific information from researchers - previous researchers. The variables measured in this study are cocoa production, cocoa prices, investment costs, cocoa operational costs, and cocoa income. The results of the data obtained will then be processed and analyzed in more depth using the analysis of investment criteria. The results of this study indicate that cocoa farming in Kopandakan II Village is feasible. With data obtained from the average Net Present Value of cocoa farming per hectare by farmers using intercropping of Rp. 6,098,333 and Rp. Rp.8,626,871 for cocoa farming using the monoculture method, the Internal Rate of Return for cocoa farming using intercropping is 19% and 20.64% for cocoa farming using monoculture. the Net B/C yield is 1.421 monoculture and 1.277 intercropping, the Payback Period cocoa farming by intercropping for 7 years 8 months and 7 years in cocoa farming by monoculture to return the investment costs incurred.